Technique Articles Are More Effective at Increasing Social Media Attention in Comparison With Original Research Articles: An Altmetrics-Based Analysis - Amar S. Vadhera, B.S; Jonathan S. Lee, B.A; Isabel L. Veloso, B.A; Harsh Singh, B.A; Nicholas A. Trasolini, M.D; Kyle N. Kunze, M.D; Safa Gursoy, M.D., Ph.D; Andrew G. Geeslin, M.D; Nikhil N. Verma, M.D; Jorge Chahla, M.D., Ph.D (Elsevier, 2022)
Purpose: To compare social media attention and citation rates between technique articles and matched original research articles (ORAs) regarding surgical procedures. Methods: All technique articles published from August 2019 through July 2020 in the free, electronic versions of Arthroscopy Techniques and JBJS Essential Surgical Techniques were matched by topic to articles in the "Original Research" sections of Arthroscopy, Sports Medicine, and Rehabilitation and JBJS Open Access in a 4:1 ratio within this time frame. The primary outcome was the Altmetric Attention Score (AAS). Secondary outcomes included citations, bibliometrics, and social media metrics. Independent t tests were used to compare primary and secondary outcomes between technique articles and ORAs. A multivariate linear regression analysis was performed to determine the association between article type and social media attention while controlling for confounding bibliometric characteristics. Results: A total of 285 matched research articles (n = 57, 20.0%) and technique articles (n = 228, 80.0%) were included. The mean AAS among all technique articles was 3.63 ± 10.08 (range, 0-96) whereas the mean AAS among all ORAs was 1.30 ± 3.98 (range, 0-25), representing a statistically significant difference (P = .016). The mean citation rate among all technique articles was not significantly different from that among ORAs (P = .73). Multivariate linear regression analysis showed a statistically significant positive association between AAS and article type, with an additional mean increase in the AAS of 2.91 (95% confidence interval, 0.04-5.77; P = .047) for every technique article compared with an ORA. Furthermore, a significant positive relation was noted between the article origin and the AAS, with an increase in the AAS of 3.00 (95% confidence interval, 0.82-5.17; P = .007) for every article published in North America compared with an article originating from another continent. Conclusions: Technique articles resulted in significantly greater AASs and social media attention in comparison with open-access ORAs on similar topics. Publications that described technical procedures in a technique journal and studies from North America were positively associated with greater AASs and greater numbers of citations received by articles. Clinical Relevance: An improved understanding of how much attention is given to technique articles versus matched ORAs by social media may influence the methods authors and journals use for distributing content. The present study suggests that one option to increase the amount of social media attention received for a particular study may be to utilize an accompanying surgical technique video or illustrations as these are easily shareable on social media and offer rapid dissemination of knowledge, similar to that of an infographic. However, physicians who view multimedia within technique articles should be encouraged to review the accompanying articles and the supporting original research as a primary source before making changes in their clinical practice.